The Influence of Job Resources Toward Employee Engagement and Its Impact On Turnover Intention of the Employees of PT Bank DKI - Tinjung Desy Nursanti; Theresha Then (Indonesia Banking School, 2018)
The purpose of this study was to determine the influence of job resources toward employee engagement and its impact on turnover intention either partially or simultaneously as well as providing advice to the management of PT Bank DKI to its employees. The method used is the associative method where data are primarily collected through interview, and distributing questionnaires to 100 employees as respondents, as well as obtaining secondary data through the study of literature. The data is processed through path analysis method. From the analysis of the data, it is found that job resources have positive and significant effect on employee engagement but, job resources has negative and not significant on turnover intention. Another result obtained is that the employee engagement has negative and significant effect on turnover intention. While simultaneously, job resources and employee engagement have negative and significant impact on turnover intention